The Gnostic Aspect of Spiritual Relations of the Elder Teenagers at Various Types of School - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2002)
The component of spiritual formation should be emphasised as if enables a person’s transcending on the basis of the truth. Attitudes of teenagers towards the gnostic values depend on many factors. One of such factors is profiled upbringing. Data show that profiled upbringing positively influences internalisation of gnostic values. The highest internalisation is at school in which profiled experience is of the greatest extent (Exact Sciences, Art, Sport (partially), and the lowest internalisation is at non-profiled schools (Comprehensive, Youth) or at schools which have just started being profiled (Humanities). The type of school determines internalisation of only some gnostic values (Gymnasium - attitude towards becoming educated; wisdom X = 3.28; Catholic school and the school of Art – attitudes towards the searching for the sense X = 2.91; 2.84) Intellectuality is the most accepted characteristic by teenagers. There is no statistically meaningful difference evaluating learning as an origin of joy and meaningfulness of one’s behaviour among schools. The weakest point of internalisation of the gnostic values is an emotional evaluating component (X = 4,33 out of seven ranks). It is possible to state that internalisation of the gnostic values of such a level cannot essentially determines spiritual formation of teenagers.